Clearing the fog a systematic review on cognitive dysfunction in COVID-19 - Butardo, Nicole D.; Coronel, Mikaela Frances D.; Dino, Alanna Marie O.; Mendoza, Tiffany Ritz F.; Sto. Domingo, Oliver Kyle D. C.; Regencia, Zypher Jude G.; Dominguez, Jacqueline C.; Baja, Emmanuel S.; Ligsay, Antonio D. (2022)
[Objective] The systematic review aims to examine the association between COVID-19 and cognitive dysfunction, including the link between the severity of COVID-19 and the occurrence of cognitive impairment and the potential pathophysiological mechanisms related to brain fog among COVID-19 patients. [Methods] PubMed, Oxford University Press, ProQuest Health and Medical Complete, ScienceDirect, Ovid, HERDIN, Google Scholar, and Cochrane Library databases were accessed to retrieve literature using the PRISMA guidelines. [Results] After critical appraisal, 13 full journal articles were included in the study. The studies showed the most frequent cognitive impairment are attention, memory, and executive function in COVID-19 patients. Compared with healthy controls in three out of four studies, cognitive impairment was only evident in COVID-19 patients. Furthermore, two studies showed no correlation between brain fog and depression, and five studies showed a link between the severity of COVID-19 infection and cognitive impairment. Cases ranging from mild to severe illness presented manifestations of brain fog. However, a disparity in the evidence of the pathophysiology of COVID-19 and cognitive dysfunction exists, prompting the need to investigate further. Additionally, recent studies provide insufficient evidence for direct central nervous system invasion, and there are emerging studies that contrast the presumed pathogenesis of neurological complications from neuroinflammation. [Conclusion] There is an association between COVID-19 and cognitive dysfunction. Manifestation of cognitive dysfunction is present regardless of illness severity. Moreover, there are existing pathophysiological mechanisms of the Coronavirus that lead to cognitive dysfunction in COVID-19 patients; however, additional studies are required to substantiate such mechanisms further. [PROSPERO registration number] CRD42022325669
Keywords: Covid-19 (Disease); SARS (Disease)